REPRESENTASI PRIMORDIALISME DALAM FILM DOKUMENTER “SEDEKAH KA BUMI” KARYA WATCHDOC - Yowana Fadhilah (Jurnal Psikotes, 2024)
Indonesia is a country with a multicultural society, which has led to the emergence of various customs or belief systems, traditions, and different social structures. The documentary film "Sedekah Ka Bumi" produced by Rendi Dwi Julianto and published by Watchdoc provides information related to one of the Sundanese customs. The purpose of this research is to analyze the representation of primordialism contained in several scenes in the documentary film "Sedekah Ka Bumi" by Watchdoc and also focuses on the customs of the Urug Traditional Village community, Bogor Regency. The representation of primordialism in this film is analyzed through Ferdinand De Saussure's semiotic theory which focuses on Signs, Markers and Signifiers. This research uses qualitative research methods. The results of this study show that the movie "Sedekah Ka Bumi" succeeded in portraying well the elements of primordialism in the culture and religion of the people of Kampung Urug. The film depicts how they maintain their traditions, religious identity, and the way they respect nature. The main message is that the traditional values applied remain relevant and respected in the modern world.